Ways to Increase the Efficiency and Efficiency of Export and Import of Fruits and Vegetables in the Republic of Uzbekistan - Nasirova Nargiza Tursunpulatovna (Genius Journals, 2023)
This article examines the export and import of fruit and vegetable products in the Republic of Uzbekistan, analyzes the characteristic features of the export of food products, identifies problems associated with the export of goods
Keywords: export; import; foreign trade